Sosialisasi Pencegahan Kejahatan Siber Bagi Karang Taruna RW 06 Pademangan Barat Jakarta Utara - Ramos, Samuel; Valentine, Hany Maria (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2022)
There are people who did not understand about the dangers posed by technology if it is not educated evenly. So that the legal problems that are often faced are related to the delivery of information, communication and transactions electronically, especially in terms of evidence and matters relating to legal actions carried out through the electronic system. For this reason, the importance of understanding Cyber ​​Crime Prevention needs to be conveyed to the community (Karang Taruna) in more depth in the RW Area 06 Pademangan Barat, North Jakarta. With this training, it is hoped that they can become internet users who can avoid the potential to become perpetrators or victims of cyber crimes.